Transtheoretical model to predict the stages of changes in smoking cessation behavior among adolescents - Park, Min Hee; Song, Hye-Young (Frontiers in Public Health, 2024)
Introduction: Previous studies on adolescent smoking cessation behavior based on the transtheoretical model have primarily focused on the development of cessation programs. Attempting to quit smoking is a prerequisite for executing smoking cessation. Appropriate methods must be selected based on the characteristics and intentions of individuals to increase smokers' satisfaction and success rates in quitting. Therefore, this study aimed to identify changing processes influencing the stages of change associated with successful smoking cessation among adolescents and examined the related factors. This descriptive study explored a transtheoretical model of different stages of changes in smoking cessation behavior among adolescent smokers. Methods: The participants included 237 middle and high school students in South Korea. We examined the differences in stages of changes in smoking cessation behaviors based on general characteristics, smoking-related characteristics, smoking cessation change processes (cognitive and behavioral), smoking decisional balance (pros and cons of smoking), and self-efficacy. Results: The probability of reaching the preparation stage of smoking cessation was significantly lower among participants who did not know their father's educational level than among those who knew their father's educational level. Conversely, this probability was significantly higher among participants whose mothers had a college or higher education level and those who did not know their mother's educational level than in those whose mothers had a high school or lower education level. Conclusion: These findings indicated that parental education is a significant predictor of the preparation stage of smoking cessation, highlighting the importance of the family environment in facilitating smoking cessation among adolescents. Accordingly, communication and support at home could help reinforce adolescents' determination to quit smoking and make relevant plans. Thus, smoking cessation support should stress the need to enhance communication at home.